2008
DOI: 10.1086/588834
|View full text |Cite
|
Sign up to set email alerts
|

The Transformation of Nesquehonite to Hydromagnesite in the System CaO-MgO-H2O-CO2: An Experimental Spectroscopic Study

Abstract: This study reports the nature of the nesquehonite-to-hydromagnesite transition at 52°C in an aqueous medium hosting magnesian calcite and nesquehonite. The latter mineral occurs with abundant calcite at the floor of the experimental chamber (substrate) and as a film of needles at the interface between the mother liquor and atmosphere (surface film). The experimental vessel was held at 52°C for 336 h and at 60°C for a further 192 h. Precipitates were analyzed by Fourier transform (FT)-Raman, augmented by FT-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(95 citation statements)
references
References 36 publications
5
89
1
Order By: Relevance
“…Power et al (2007) reported dypingite formation in biotic mesocosm experiments, and nesquehonite formation in abiotic control experiments at a pH of $9.5. The transformation of nesquehonite to hydromagnesite is known to occur through intermediary hydrous magnesium carbonate phases such as dypingite (Davies and Bubela, 1973;Hopkinson et al, 2008). Although it has been argued that such mineralogical changes could be an artifact of the sample drying (Botha and Strydom, 2001), we did not observe any significant difference in the XRD patterns of samples prepared via freeze-drying and those oven-drying at 50°C, and thus conclude that mineralogical changes did not occur during sample preparation.…”
Section: Magnesium Isotopic Compositioncontrasting
confidence: 49%
“…Power et al (2007) reported dypingite formation in biotic mesocosm experiments, and nesquehonite formation in abiotic control experiments at a pH of $9.5. The transformation of nesquehonite to hydromagnesite is known to occur through intermediary hydrous magnesium carbonate phases such as dypingite (Davies and Bubela, 1973;Hopkinson et al, 2008). Although it has been argued that such mineralogical changes could be an artifact of the sample drying (Botha and Strydom, 2001), we did not observe any significant difference in the XRD patterns of samples prepared via freeze-drying and those oven-drying at 50°C, and thus conclude that mineralogical changes did not occur during sample preparation.…”
Section: Magnesium Isotopic Compositioncontrasting
confidence: 49%
“…The three bands at 1520, 1466.06, 1420.06 cm -1 are ascribed to the split v3 antisymmetric stretching mode (Kloprogge et al, 2003;Coleyshaw et al, 2003;Morgan et al, 2015).The stretching of the O-H and the H2O molecule gives rise to broad bands in the region between 2500-4000 cm -1 (Ferrini et al, 2008;Kloprogge et al, 2003). The bands at 3326.33, 3455.14, 3564.25 cm -1 can be ascribed to OH-stretching modes of water in the crystal structure of the nesquehonite (Hopkinson et al, 2012;Hopkinson et al, 2008). At 1653.43 cm -1 a H-O-H bending band is observed, which is associated with structural H2O (Lanas and Alvarez, 2004;Hopkinson et al, 2008;Hopkinson et al, 2012) and absorbed H2O (Kloproggre et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The bands at 3326.33, 3455.14, 3564.25 cm -1 can be ascribed to OH-stretching modes of water in the crystal structure of the nesquehonite (Hopkinson et al, 2012;Hopkinson et al, 2008). At 1653.43 cm -1 a H-O-H bending band is observed, which is associated with structural H2O (Lanas and Alvarez, 2004;Hopkinson et al, 2008;Hopkinson et al, 2012) and absorbed H2O (Kloproggre et al, 2003). The two peaks observed at 699.97 cm -1 and 607.12 cm -1 are assigned to the v4 in-plane bending mode of the HCO3…”
Section: Resultsmentioning
confidence: 99%
“…NaHCO3/ Na2CO3 solutions would be obtained when NaOH is used for the dissolution of CO2 into an aqueous solution but other bases such as aqueous ammonia solutions have been also used (Ferrini et al, 2009;De Vito et al, 2012). The physical chemistry of the precipitation of MHCH phases has been much studied and it appears that metastability is widespread among the precipitated products (Dell and Weller, 1959;Bender and Sprague, 1965;Langmuir, 1965;Davies and Bubela, 1973;Canterford et al, 1984;Haenchen et al, 2008;Hopkinson et al, 2008Hopkinson et al, , 2012Case et al, 2011;Ballirano et al, 2013).…”
Section: Mhch Phasesmentioning
confidence: 99%